Transfusion-transmissible infections among blood donors in Bejaia, Algeria: ten years retrospective and comparative study - Djoudi, Ferhat; Amir, Nadir; Chouikh, Mohammed Tahar (The Journal of Infection in Developing Countries, 2023)
Introduction: Blood transfusion saves millions of lives year around the world; it is the most important life-saving option for blood recipients. However, this act is not without risks as contaminated blood may be the source of transfusion-transmissible infections (TTI). This is a retrospective and comparative study on the prevalence of acquired human immunodeficiency syndrome, viral hepatitis B, C and syphilis in blood donors from Bejaia province (Algeria). Methodology: This study is designed to estimate the risk of TTIs among blood donors and the demographic associated factors. It was carried out in the serology laboratories of Bejaia blood transfusion center and Khalil Amrane university hospital. Data were collected from the archived results of screening tests for HBV, HCV, HIV and syphilis, mandatory for all blood donations, from January 2010 to December 2019. The association was considered statistically significant at p < 0.05. Results: Among 140,168 donors from Bejaia province, 78,123 represent the urban population and 62,045 the rural population. Over 10 years, results of serological tests revealed a prevalence of 0.077%, 0.083%, 0.102%, and 0.132%, respectively for HIV, HCV, HBV, and Treponema pallidum. Trends of hepatitis B and syphilis were decreasing; however, hepatitis C was increasing. Conclusions: HIV and syphilis prevalence have been variable, with significant peaks in 2013 and 2014, respectively. Globally, the low rates reported in this study confirm the effectiveness of the preventive policy applied by the health authorities. However, among the rural population, special attention is required to stem any resurgence of hepatitis C and syphilis.